Implementasi Pasal 31 Kompilasi Hukum Islam Tentang Penetapan Jumlah Mahar : (Studi Kasus Keluarga Perumahan Pesantren Attahdzib) - Latifah, Hanik; Naachy, Dzin Nun (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
This study explores the determination of the dowry amount in marriages within the Attahdzib Pesantren housing community. Using a normative-philosophical approach and sociological impact analysis, this research highlights the application of simplicity and ease principles in KHI (Compilation of Islamic Law). The methodology includes field observations and interviews with married couples. The results show that a simple yet meaningful dowry supports social stability and strengthens women's position in marriage. These findings suggest that applying Islamic principles on dowry can create harmonious and socially stable family relationships.